Modified Delphi Technique: The Development of Measurement Model for Innovative Instructional Leadership in Technical and Vocational Education Systems - Mat Nashir, Irdayanti; Mustapha, Ramlee; Mohd Imam Maarof, Nurul Nazirah; Jing Rui, Tang (Journal of Technical Education and Training, 2020)
This study aimed to determine the constructs and to develop measurement model of innovative instructional leadership for polytechnics system in Malaysia. The study used Hallinger and Murphy model as the underpinning theoretical framework. This study has utilized a model development approach as its research design. In the earlier stage, a Modified Delphi technique was used to gather initial data regarding innovative instructional leadership. Eleven experts were selected based on their expertise and experience. They confirmed 13 constructs of innovative instructional leadership for the polytechnics system. Stratified random sampling was used in this study to select the respondents. A new instrument was developed which consisted of 13 constructs and 188 items and distributed to the respondents in the selected polytechnics to determine the innovative instructional leadership of the polytechnic administrators. Empirical data collected were analyses using descriptive and inferential statistics that included confirmatory factor analysis. The results showed that lecturers at the polytechnics did not agree that their administrators possess the innovative instructional leadership particularly related to strategic thinking, innovative thinking and network management. In addition, the study also found that the administrators of the polytechnics have moderate level of innovative instructional leadership for most of the constructs. Based on confirmatory factor analysis, it was found that only 68 items out of 188 items that are important to the innovative instructional leadership in the polytechnics system in Malaysia. In conclusion, this research study has obtained nine importance of innovative instructional leadership in the polytechnic system in Malaysia. Importance of acquired is expected to improve the technical competence of the organization, particularly polytechnics to achieve the aspirations outlined transformation. In addition, these studies also acquire instruments for innovative instructional leadership to guide the administrator to assess the weaknesses and constraints existing in themselves. It is hoped that the results of this study could assist the top management in polytechnics to spearhead the direction and leadership of the polytechnics towards a more creative and innovative system in line with the government’s desire to transform the polytechnic system to becoming a preferred choice of higher education institution.